(untitled) (Anclajes, 2021)
This review examines the advances, changes and critical setbacks that occurred in the field of memory and violence in post-dictatorship Southern Cone. Many of the contributions published in Anclajes in the last decades make up a corpus of interest for the research of historical and cultural memory.